Regulatory T cell differentiation: cooperation saves the day. (24th February 2015) - Liston, Adrian; Schlenner, Susan M
<x xml:space="preserve">Abstract</x> MicroRNA are important regulators of CD4 T cell differentiation, altering the balance between the immunogenic and tolerogenic pathways. Studies in mice with microRNA‐deficient T cells have revealed defects in differentiation into the regulatory T cell lineage; however, the individual microRNA responsible have remained elusive. A recent paper in The EMBO Journal uses a systematic screen to find a novel cooperative action between an inducible and a constitutive microRNA in aiding regulatory T cell induction.